Does New Urbanism “Just Show Up”? Deliberate Process and the Evolving Plan for Markham Centre - Perrott, Katherine (2020)
This article traces three decades of planning for a Canadian suburban downtown in Markham, Ontario, an early adopter of new urbanism. While leading new urbanist design firm Duany Plater-Zyberk & Co. (also known as DPZ) produced site plans for both Cornell and Markham Centre, much of the research attention on the implementation of new urbanism has focused on the Cornell development, where build-out began in the 1990s. Construction was delayed in Markham Centre until a decade later and continues today. The article is empirically grounded in a discourse analysis of policy, housing advertisements, and interviews with key actors in the planning and development process. New urbanism’s popular influence has led Fulton (2017) to argue that a ubiquitous urbanism now “just shows up.” Mainstreaming of new urbanist principles and the discursive framing of planning for Markham Centre as an ‘evolution’ further underscores this perception. Key actors describe an ‘organic’ planning process illustrating how the plan has changed in response to shifting market dynamics, political interests, and funding opportunities. The article explores the discourse about new urbanism and argues that in Markham Centre new urbanism has not just shown up, but has rather required a deliberate, collaborative, and adaptable process. Development that is transit oriented and attractive to knowledge economy workers underpins the contemporary vision. New urbanism as a label is losing relevance in Markham, where sprawl represents the past, new urbanism describes the legacy of 1990s planning, and a ‘real’ competitive urbanism is the vision for the future.